Safety and efficacy of eltrombopag plus pulsed dexamethasone as first‐line therapy for immune thrombocytopenia. (13th January 2020) - Zhang, Lunqing; Zhang, Mingjie; Du, Xin; Cheng, Yunfeng; Cheng, Gregory
Summary: Current first‐line treatments for immune thrombocytopenia (ITP) usually have transient effects and sustained platelet response off therapy remains low. We evaluated whether eltrombopag plus pulsed dexamethasone as first‐line therapy can increase the proportion of patients maintaining platelet counts >50 × 10 9 /l for a prolonged period without further ITP therapy. Treatment consisted of eltrombopag 25–75 mg daily according to platelet response for 12 weeks plus dexamethasone, 40 mg daily for four consecutive days every four weeks for 1–3 courses. Primary endpoint was durable response off therapy defined as maintaining platelet counts >50 × 10 9 /l for more than six months without further ITP therapy. Fifty ITP subjects were enrolled between November 2014 and March 2019. Out of 46 evaluable subjects, 26 (56·5%) had achieved the primary endpoint. The median platelet counts at six months off‐treatment follow‐up were 158 × 10 9 /l. Only two out of 26 responders had relapsed at eight‐ and nine‐month follow‐up. The remaining 24 are still maintaining platelet counts >50 × 10 9 /l, the longest over three years. All subjects tolerated treatment well and no Grade 3 or above adverse effects were reported. Eltrombopag plus pulsed dexamethasone as a first‐line therapy could result in durable response off therapy in a significant number of ITP subjects.